A Qualitative Study on the Management of Personal Protective Equipment (PPE) During the COVID-19 Pandemic - Ayuli Fardila Sari ZA (Journal of Health Sciences and Epidemiology, 2023)
Based on a preliminary study, the COVID-19 PPE at Rawang Primary Health Care (PHC) was only partially available. The purpose of this research was to analyze the management of COVID-19 personal protective equipment (PPE) for Rawang PHC officers in Padang City. This research was a qualitative study held in July-September 2021 at the Rawang PHC. Research informants were four officers of PHC, who were obtained through purposive sampling. Collecting data was done through in-depth interviews, document reviews, and observation—data analysis using content analysis with source and method triangulation. The results of this study show that planning for needs was carried out using the consumption method; requests for COVID-19 PPE were made to the Padang District Health Office, which can be done at any time. Receipt of PPE COVID-19 by recording and checking the amount of PPE on the stock card. PPE storage using the FIFO method. The destruction of PPE was only done at the beginning of the pandemic. The distribution of PPE was carried out in sub-units and PHC networks. Control carried out related to the supply and use of PPE. The recording and reporting of PPE have been carried out, but the evaluation has yet to be carried out because the PHC still needs to have a Standard Operating Procedure (SOP) for managing COVID-19 PPE. The management of COVID-19 PPE at the Rawang PHC could be more optimal. It is recommended for Rawang PHC to make a SOP for the management of COVID-19 PPE.